Recovery-based services in a psychiatric intensive care unit – the consumer perspective. (October 2015) - Ash, David; Suetani, Shuichi; Nair, Jayakrishnan; Halpin, Matthew
Objective: To describe the implementation of recovery-based practice into a psychiatric intensive care unit, and report change in seclusion rates over the period when these changes were introduced (2011–2013). Method: Recovery-based practices including collaborative care, safety care plans, a comfort room, and debriefing after coercive interventions were introduced. A carer consultant was employed. A restraint and seclusion review committee, chaired by a peer worker, was established. A consumer exit interview was introduced and these data were collected, reviewed by staff and the peer worker and used to improve the ward environment. Rates of seclusion were measured during the period when recovery-based practices were introduced. Results: Consumer feedback indicated that positive aspects of the psychiatric intensive care unit included approachable, helpful staff and completion of a safety care plan. Negative aspects included lack of involvement in decisions about admission and about medications, the non-smoking policy, and being placed in seclusion or restraint. There was a significant reduction in the number of consumers secluded and the total number of seclusions. Conclusions: Recovery principles can be successfully introduced in a psychiatric intensive care unit environment. Introduction of recovery based practice was associated with a reduction in seclusion.